Evaluación del nicho ecológico deformas larvales de Aedes aegypti y Culex quinquefasciatus (Díptera: Culicidae) en una comunidad urbana de San José, Costa Rica - Calderón Arguedas, Ólger (2007)
Observations related to the width and overlap of the ecological niche for larval forms of Aedes aegypti and Culex quinquefasciatus in artificial containers were performed using the data obtained during two laval surveys in the four sectors of the neighborhood “La Carpio”, San José, Costa Rica. “La Carpio” was the first community of the Metropolitan Area of San José that suffered a dengue outbreak. The first survey was performed in the dry season of 2003 and the second one in the wet season of the same year. The width of niche was expressed using the Levin Index, and the overlap of niche was determined by the Morisita Index modified by Horn. In both larval surveys Ae. aegypti and Cx. quinquefasciatus were present. Ae. aegypti showed higher values for width of niche in the four sectors of the neighborhood and during both surveys.During the first larval survey (dry season of 2003), there was an overlap of niche only in sectors 1 and 3. In the wet season, the overlap was observed in the four sectors, but the values were higher in sectors 1 and 2. Results show that Ae. aegypti is the most common species of mosquitoes in artificial containers in the neighborhood, and that the role of Cx. quinquefasciatus as modulator of the Ae. aegypti populations could be limited